THE INFLUENCE OF JIGSAW STRATEGY TO STUDENTS’ READING COMPREHENSION - Sinta Apriana; Rahma Dianti (Didascein : Journal of English Education, 2020)
This study highlighted the implementation of jigsaw strategy to improve eleventh graders’ reading comprehension at SMA Karya Ibu Palembang. Jigsaw is one of learning strategies under cooperative learning method that promotes group work and problem solving practice among the group members. This strategy encourages each member to focus on solving a given task in a reading practice. The objective of this study was to find out whether or not jigsaw strategy could significantly improve students’ reading comprehension of explanation text. It examined the influence of Jigsaw strategy on students’ reading achievement. Pre-experimental research design was administered as the research method since it had no control group involved. 35 students of eleventh grade that categorized low in reading achievement, participated as the sample of this study. A reading comprehension test, consisting of 20 items of multiple choice, used as the data collection technique. The obtained data was analyzed using Paired Sample T-Test. Research finding showed that Jigsaw strategy could significantly improve students’ reading comprehension.  The result of Paired Sample T-Test revealed that the value of t-obtained (8.864) was higher than the value of t-table (2.032) and the significance level (2-tailed) was 0.000. It indicated that jigsaw strategy contributed significant influence toward students’ reading comprehension.Keywords: jigsaw, reading comprehension, cooperative learning